Analisis Pemahaman Siswa SMA Pada Materi Larutan Elektrolit Dan Non Elektrolit - Dhini Nayla Rahmadhany; Hana Yasmin Putri; Nawwafa Azhar Raudah; Sandea Arianisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
It’s very important for students to be able to understand the basic concepts of chemistry and how they relate to one concept to another. The purpose of this study is to evaluate and examine the nderstanding of grade XI MA Al Rohmah students in Tasikmalaya for understanding the concept of electrolyte and non electrolyte solutions. Descriptive research methodology with a quantitative approach is used. The study involved 22 students who were taken as samples by researchers. Data collection was conducted through an online questionnaire-based test consisting of 7 multiple-choice questions with Yes/No options. The results showed that 18 students (81.81%) had the ability to understand the concept of electrolyte and non-electrolyte solutions very well. But there are still 4 students (18.19%) who still do not understand the basic concepts of electrolyte and non-electrolyte solution materials. This shows that a more interactive and in-depth learning approach is needed to increase students' understanding of electrolyte and non electrolyte solution materials which include phases and chemical bonds in a compound that can affect its electrolyte properties, lamp flame tests on electrolyte and non electrolyte compounds, and the ionization process of electrolyte and non-electrolyte solutions to strengthen the basic concepts of student chemistry.